Lands of wonder Europe to Africa - Elder, Stephen; JWM Productions ([S.l.] : JWM Productions, 2000)
Take a thrilling journey to four of the greatest natural treasures of Europe and Africa. They are the legendary Giant's Causeway of Ireland's rocky noerthern coast ; elusive mountain gorillas in Uganda ; stunning snow-capped peaks of Italy ; and spectacle of thundering herds of migrating wildbeest, zebra and gezelle on Africa's fabled Serengeti Plains.
Executive producer, Wendy Maple ; editor, Clifford Hoelscher
Narrator: Nigel Anthony
Keywords: National parks and reserves; Wildlife conservation